A strategy to control the grain boundary density and Cu+/Cu0 ratio of Cu-based catalysts for efficient electroreduction of CO2 to C2 products. Issue 5 (25th February 2020) - Chen, Chunjun; Sun, Xiaofu; Yan, Xupeng; Wu, Yahui; Liu, Mingyang; Liu, Shuaishuai; Zhao, Zhijuan; Han, Buxing
Abstract : Cu(OH)2 /CuO nanocomposite-derived Cu2 O/Cu achieves a total faradaic efficiency for C2 products of 65% via tuning the grain boundary density and Cu + /Cu 0 ratio. Abstract : Cu(OH)2 /CuO nanocomposite-derived Cu2 O/Cu was highly efficient for CO2 electroreduction to C2 products. The highest faradaic efficiency and current density could reach 64.5% and 26.2 mA cm −2, respectively. By changing the calcination time, moderate grain boundary density and the Cu + /Cu 0 ratio in catalysts can be controlled, leading to a large number of active sites and low interfacial charge transfer resistance.